Characterization of Quantitative Trait Loci for Leaf Rust Resistance from CI 13227 in Three Winter Wheat Populations - Zhao, Lanfei; Lu, Yue; Zhang, Xiaocun; Zhao, Wei; Xu, Xiangyang; Wang, Hongliang; Zhang, Guorong; Fritz, Allan K.; Fellers, John; Guttieri, Mary; Jordan, Katherine W.; Bai, Guihua (Phytopathology, 2024)
Leaf rust is a widespread foliar wheat disease causing substantial yield losses worldwide. Slow rusting is “adult plant” resistance that significantly slows epidemic development and thereby reduces yield loss. Wheat accession CI 13227 was previously characterized as having slow-rusting resistance. To validate the quantitative trait loci (QTLs) and develop diagnostic markers for slow rusting resistance in CI 13227, a new population of recombinant inbred lines of CI 13227 × Everest was evaluated for latent period, final severity, area under the disease progress curve, and infection type in greenhouses and genotyped using genotyping-by-sequencing. Four QTLs were identified on chromosome arms 2BL, 2DS, 3BS, and 7BL, explaining 6.82 to 28.45% of the phenotypic variance for these traits. Seven kompetitive allele-specific polymorphism markers previously reported to be linked to the QTLs in two other CI 13227 populations were validated. In addition, the previously reported QLr.hwwg-7AL was remapped to 2BL (renamed QLr.hwwg-2BL) after adding new markers in this study. Phenotypic data showed that the recombinant inbred lines harboring two or three of the QTLs had a significantly longer latent period. QLr.hwwg-2DS on 2DS showed a major effect on all rust resistance traits and was finely mapped to a 2.7-Mb interval by two newly developed flanking markers from exome capture. Three disease-resistance genes and two transporter genes were identified as the putative candidates for QLr.hwwg-2DS. The validated QTLs can be used as slow-rusting resistance resources, and the markers developed in this study will be useful for marker-assisted selection.